2017
DOI: 10.1002/pssc.201700156
|View full text |Cite
|
Sign up to set email alerts
|

Strain and Compositional Analysis of (Si)Ge Fin Structures Using High Resolution X‐Ray Diffraction

Abstract: The performance of heterogeneous 3D transistor structures critically depends on the composition and strain state of the buffer, channel, and source/drain regions. In this paper we discuss the value of in‐line high resolution X‐ray diffraction (HRXRD) measurements based on three representative examples. First, we analyzed the strain state of etched Ge fins in the two in‐plane directions. We could verify a loss in channel strain after growth of a Si cap which we attribute to Ge reflow. Secondly, we studied the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Compressive uniaxial strain is preferred for pFET mobility and has been confirmed for the replacement channel fabrication scheme (STI first) 6,7,31 as well as the STI last fabrication scheme. 19,32 The out-of-plane lattice constant (in vertical direction) shows a larger lattice constant with respect to relaxed Ge, as verified by symmetric (004) ω -2 XRD scans. 32 After growing a 3-10 ML thick Si passivation layer on top of the strained Ge fin surfaces, the Ge peak shows a shift to smaller ω -2 (Fig.…”
Section: Epitaxial Growth Of Ultra-thin Si Passivation Layers On Stra...mentioning
confidence: 64%
See 1 more Smart Citation
“…Compressive uniaxial strain is preferred for pFET mobility and has been confirmed for the replacement channel fabrication scheme (STI first) 6,7,31 as well as the STI last fabrication scheme. 19,32 The out-of-plane lattice constant (in vertical direction) shows a larger lattice constant with respect to relaxed Ge, as verified by symmetric (004) ω -2 XRD scans. 32 After growing a 3-10 ML thick Si passivation layer on top of the strained Ge fin surfaces, the Ge peak shows a shift to smaller ω -2 (Fig.…”
Section: Epitaxial Growth Of Ultra-thin Si Passivation Layers On Stra...mentioning
confidence: 64%
“…19,32 The out-of-plane lattice constant (in vertical direction) shows a larger lattice constant with respect to relaxed Ge, as verified by symmetric (004) ω -2 XRD scans. 32 After growing a 3-10 ML thick Si passivation layer on top of the strained Ge fin surfaces, the Ge peak shows a shift to smaller ω -2 (Fig. 6a).…”
Section: Epitaxial Growth Of Ultra-thin Si Passivation Layers On Stra...mentioning
confidence: 64%
“…However, the situation might be different for fin patterned wafers as the thermal steps are typically applied after fin patterning during which elastic relaxation is expected to occur. 13 We have also observed that peculiar relaxation mechanisms occur at wafers edges. In the case of Si 0.7 Ge 0.3 grown on 300 mm Si(001) wafers, more than 200 nm thick SiGe layers could be grown relaxation-free at the center of the wafer.…”
Section: Epitaxy For Channel and Source/drain Materialsmentioning
confidence: 67%
“…For Si 1-x Ge x fins grown on Si(001) or Si 1-y Ge y (001) Strain-Relaxed Buffers (SRB), Si 1-x Ge x relaxation should be avoided to keep defectivity under control and preserve the longitudinal strain along the channel. 13 In reference 13, the authors have studied the relaxation behavior of 20 nm wide and 30 nm high Ge fins patterned from Ge blanket layers grown on a Si 0.32 Ge 0.68 SRB. The pitch (distance between two fins) was 45 nm.…”
Section: Epitaxy For Channel and Source/drain Materialsmentioning
confidence: 99%
See 1 more Smart Citation